Implementation of Progressive Muscular Relaxation (PMR) Method to Labor Pain on Mother’s Fisrt Stage Active Phase of Labor in Endang Sutikno Midwife Clinic Kediri City - Pratamaningtyas, Susanti (Jurnal IDAMAN (Induk Pemberdayaan Masyarakat Pedesaan), 2020)
Labor pain starts in the first stage of labor which caused by uterus contraction. Labor pain brings concerns for mothers who will choose cesarean section instead normal delivery. The anxiousness, tired and stressed in labor can cause inadequate uterine contractions which will lead to prolonged labor, which can endanger both mother and baby. This study was aimed to determine the effect of the implementation of the progressive muscular relaxation method on labor pain during the first stage, active phase of the labor. The research method was carried out on 40 respondents by measuring the intensity of the pain beforehand, then after applied the PMR method, the intensity of the pain was measured again. The instrument used was behavioral observation sheet. The results of the study showed that from 8% respondents with mild pain, after given PMR method, there was 76% respondents with mild pain, and there was no unbearable pain and severe pain from 36% respondents reduced to 4%. Based on these results, there were changes in the level of pain that felt by mother after using PMR method. It’s hoped that this method can always be applied so that mothers can undergo the labor process comfortably and smoothly